Professionalism in Management Education: Is the Emperor Naked in the 1990s? - Harrigan, Kathryn Rudie (Academy of Management Review, 1990)
The article reviews the book ?Management Education & Development: Drift or Thrust Into the 21st Century?? by Lyman Porter and Lawrence McKibbin.